Dopamine agonists early monotherapy for the delay of development of levodopa-induced dyskinesias. (February 2014) - Stathis, Pantelis; Konitsiotis, Spiridon; Antonini, Angelo
<x xml:space="preserve">Abstract</x> Dyskinesias are common, often disabling motor complications emerging in Parkinson's disease following chronic levodopa treatment. Common views associate the development of dyskinesias both with progressive loss of striatal dopamine nerve terminals and with intermittent delivery of the short half-life levodopa. Thus, according to continuous dopaminergic stimulation theory, dopamine agonists having half-lifes longer than levodopa would minimize the risk of the development of dyskinesias. The article highlights some interesting aspects of the clinical trials testing dopamine agonists monotherapy as a strategy that can reduce the risk of motor complications, and raises some concerns in terms of their early use in Parkinson's disease treatment to prevent or delay dyskinesia. Finally, we emphasize the need for reconsideration of arguments against use of levodopa as a starting therapy for Parkinson's disease.